Study protocol: evaluation of an online, father-inclusive, universal parenting intervention to reduce child externalising behaviours and improve parenting practices - Tully, Lucy A. (BMC Psychol, 2017)
BACKGROUND: Parenting interventions that focus on enhancing the quality and consistency of parenting are effective for preventing and reducing externalising problems in children. There has been a recent shift towards online delivery of parenting interventions in order to increase their reach and impact on the population prevalence of child externalising problems. Parenting interventions have low rates of father participation yet research suggests that father involvement may be critical to the success of the intervention. Despite this, no online parenting interventions have been specifically developed to meet the needs and preferences of fathers, as well as mothers. This paper describes the protocol of a study examining the effectiveness of an online, father-inclusive parenting intervention called ‘ParentWorks’, which will be delivered as a universal intervention to Australian families. METHODS/DESIGN: A single group clinical trial will be conducted to examine the effectiveness of ParentWorks for reducing child externalising problems and improving parenting, as well as to explore the impact of father engagement (in two-parent families) on child outcomes. Australian parents/caregivers with a child aged 2–16 years will be recruited. Participants will provide informed consent, complete pre-intervention measures and will then complete the intervention, which consists of five compulsory video modules and three optional modules. The primary outcomes for this study are changes in child externalising behaviour, positive and dysfunctional parenting practices and parental conflict, and the secondary outcome is changes in parental mental health. Demographic information, satisfaction with the intervention, and measures of parental engagement will also be collected. Questionnaire data will be collected at pre-intervention, post-intervention and three-month follow-up, as well as throughout the program. DISCUSSION: This paper describes the study protocol of a single group clinical trial of a national, online, father-inclusive parenting intervention. The results from this study could be used to inform public policy about providing support to parents of children with behaviour problems, and enhancing the engagement of fathers in parenting interventions. TRIAL REGISTRATION: ACTRN12616001223426, registered 05/09/2016